Williams Whithers, The economic crisis of Latin America, New York, The free press of Glencoe - Collier - MacMillan Limited. 1964. - Denis, Paul Yves (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Geografía, 1965)

(untitled)
Fil: Denis, Paul Yves. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras